Thermal Management Technologies: Anomalously Low Heat Conduction in Single‐Crystal Superlattice Ceramics Lower Than Randomly Oriented Polycrystals (Adv. Mater. Interfaces 7/2021). Issue 7 (9th April 2021) - Cho, Hai Jun; Wu, Yuzhang; Zhang, Yu‐Qiao; Feng, Bin; Mikami, Masashi; Shin, Woosuck; Ikuhara, Yuichi; Sheu, Yu‐Miin; Saito, Keiji; Ohta, Hiromichi
Abstract : In article number 2001932, Hai Jun Cho, Hiromichi Ohta, and co‐workers discovered defied common wisdom that heat conduction in single‐crystals is significantly reduced more than randomly oriented polycrystals by introducing the superlattice structures with a period of several nm.